STRATEGI PENERAPAN Al-LU‘BAH AL-LUGAWIYAH DALAM PEMBELAJARAN MUFRADAT - Hurriyatus Sa'adiyah; Saputra, Indra; Aniati, Ira; Nara Pranata Deviona; Mardi Yati (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
This study intends to: 1) clarify how language games might be used for the learning of vocabulary and 2) understand the supporting and inhibiting factors encountered in using language games. To achieve this goal, the writer uses qualitative research methods using case studies. The results showed that the language game used in SDIT Qurata A'yun 1 was a rotating clock game. Three phases are included in the Language Implementation Strategy for this School; planning, implementation and evaluation. There are two inhibiting factors or obstacles in the application of language games, namely time, and the situation in which some students can't understand the content and look uninterested during play language game. In the meantime, in order to be able to carry out this game, there are two drivers: internal factors; teachers' and students' skills or external factors such as facilities and infrastructure. The use of language games is hindered by two factors, namely time and the situation in which some students are unable to understand the content and are not interested in playing the language game.